Case Report: long-term misdiagnosis and follow-up of a patient with HNF4A-MODY carrying a new de novo mutation - Luo, Jing; Li, Ai; Wang, Xiaoli (Frontiers in Endocrinology, 2025)
BackgroundHNF4A-MODY constitutes 5%–10% of MODY cases; however, treatment options remain unclearly recommended, and long-term follow-up of patients with HNF4A-MODY is lacking due to limited research. Here, we report a case carrying a new de novo variant of HNF4A. The patient had been using insulin for up to 25 years before genetic diagnosis.Case descriptionA 38-year-old man sought consultation due to an increased daily insulin requirement and inadequate glycemic control. At the age of 13, the patent’s parents discovered that he had significantly elevated fasting blood glucose levels accompanied by weight loss. He was subsequently diagnosed with type 1 diabetes and began insulin therapy. At a routine follow-up at age 21, another physician observed that his pancreatic islet function remained preserved, with negative results for diabetes-related antibodies. Consequently, his diagnosis was revised to type 2 diabetes, and the antihyperglycemic therapy was added in metformin and acarbose. Before the current consultation, the patient’s insulin dosage had gradually increased to 80 units per day; however, glycemic control remained unsatisfactory. Whole exome sequencing identified a heterozygous variant, c.272G > A (p.R91H), in exon 3 of the HNF4A gene (NM_175914.5) in the patient. The patient’s treatment regimen was modified to include metformin at a dosage of 1.0 g twice daily, semaglutide at 0.5 mg once weekly, and insulin glargine was gradually discontinued. The patient achieved adequate glycemic control during follow-up.ConclusionThis case emphasizes that spontaneous HNF4A-MODY is prone to misdiagnosis and the prolonged rate of pancreatic function decline in HNF4A-MODY. Glycemic control and complication progression could be acceptable in HNF4A-MODY cases treated with long-time insulin, but risks of hypoglycemic events, obesity, and atherosclerosis remain. Switching to GLP1RA treatment in HNF4A-MODY still yields a good effect after a prolonged disease course.